N6-methyladenosine RNA methylation, a new hallmark of metabolic reprogramming in the immune microenvironment - Li, Xiaoyue; Peng, Lin; Yang, Xuelian; Luo, Jing; Wang, Jianmei; Mou, Kelin; Zhou, Huan; Luo, Yuhao; Xiang, Li (Frontiers in Immunology, 2024)
N6-methyladenosine is one of the most common and reversible post-transcriptional modifications in eukaryotes, and it is involved in alternative splicing and RNA transcription, degradation, and translation. It is well known that cancer cells acquire energy through metabolic reprogramming to exhibit various biological behaviors. Moreover, numerous studies have demonstrated that m6A induces cancer metabolic reprogramming by regulating the expression of core metabolic genes or by activating metabolic signaling pathways. Meanwhile, m6A modifications and related regulators are key targets in the regulation of immune effects. We further summarize how m6A modifications contribute to tumor metabolism, and how these events affect the tumor immune microenvironment, with a specific focus on different cell types. Finally, we focus on the specific applications of this field to tumor immunotherapy. We review the potential role of m6A in metabolic reprogramming of tumor immune microenvironment and its regulatory mechanism, with the aim of providing new targets for tumor metabolic regulation and immunotherapy.